Sikap terhadap pelajar bermasalah pendengaran di kalangan guru sekolah pendidikan khas = Attitude towards hearing impaired students among special school teachers - Ismail, Noraidah; M, Suzana (Penerbit Fakulti Sains Kesihatan Bersekutu, Universiti Kebangsaan Malaysia, 2000)
The aim of this study was to examine special school teachers toward hearing impaired students. A total of 38 teachers were chosen as subjects of this study. The teachers’ attitude was measured based on their training, teaching experience age and gender. Attitude towards Deafness Scale was used to measure the teachers’ attitude towards hearing impaired students. Data was analyzed using t-test and one-way analysis of variance (ANOVA). Result showed that there were significant difference in attitude towards hearing impaired students based on the teachers’ training and their age but no significant differences based on gender and teaching experience.